Rheological aspects of bioconvective flow of radiated ternary hybrid nanofluid toward porous stretched cylinder with activation energy and heat generation - Haq, Fazal; Ghazwani, Hassan Ali; Ghazwani, Mofareh Hassan (Journal of thermal analysis and calorimetry, 2025)
Ternary hybrid nanofluids (THNFs) are an advanced class of nanofluids that combine various types of nanoparticles within a conventional carrier liquid to enhance heat transfer performance. These fluids are extremely interested in medicinal technologies, energy systems, and thermal engineering applications because of their superior rheological, thermal, and transport properties compared to conventional fluids. Owing to practical usages and novel features of THNFs, the current paper aims to scrutinize the performance of these fluids to enhance the efficiency of modern-day devices. Engine oil is considered as base fluid. The hybrid nanofluid (HNF) is developed with the uniform immersion of cobalt ferrite CoFe 2 O 2 , and aluminum oxide Al 2 O 3 into base liquid, while THNF is formulated by adding copper Cu nanoparticles into HNF. Effects of magnetic field and surface porosity are considered in the formulation of the momentum equation. Consequences of heat generation, radiation, dissipation, chemical reaction, and Arrhenius kinetics are accounted in the mathematical formulation. The flow governing system of PDEs is altered into ODEs and then treated numerically via RKF-45 (Runge–Kutta Fehlberg scheme). The behavior of HNF and THNF velocity, thermal field, skin friction coefficient, mass concentration, density number, local heat transfer rate, and Sherwood number versus sundry variables is examined in detail. Findings show that the thermal field upsurges through higher Hartmann and Eckert numbers while it decays via rising Prandtl number. Mass concentration boost via activation energy variable whereas an opposite trend is noticed in case of chemical reaction variable. Additionally, it is noticed that motile density is a decreasing function of bioconvection Peclet and Lewis numbers.